Improvement of soybean yields using organic fertilizer enriched with microbes under dry land condition of Banten Province. Issue 3 (June 2021) - Yuniarti, S; Mulyaqin, T; Hadiatry, M C; Purba, R
Abstract: The objective of the present study was to determine the yield and growth of soybeans using organic fertilizers enriched with microbes under dryland conditions. The research was carried out in the Pandeglang Regency of Banten Province. A randomized block design was used using 4 treatments, and 6 replications. The treatments were fertilization, namely without fertilizer (control/P1); 3 ton/ha of chicken manure (P2); 3 ton/ha of chicken manure, and recommended inorganic fertilizer (P3); 1 ton/ha of organic fertilizer enriched with microbes, and recommended inorganic fertilizer (P4). The soybean variety used was the Anjasmoro variety. The parameters observed were the length of root, the height of plant, the nodules number, root weight at age 65 days after planting (DAP), the filled pods' number, and the soybean yield. The research results showed that the treatment of organic fertilizer enriched with microbes (P4) gave a higher growth response based on the value of the height of the plant, the length of root, the number of nodules, and the number of filled pods, compared to other treatments. It increased soybean yield from 1.58 ton/ha up to 2.61 ton/ha.